Manufacturing method for preparing organic packaging ceramic substrate from co-fired ceramic

By using a co-fired ceramic preparation method, combined with multilayer green ceramic sheet technology using ceramic slurry and metal conductor slurry, the problem of insufficient thermal conductivity and insulation of traditional packaging substrates in high-power, high-frequency and high-temperature scenarios has been solved, realizing a ceramic core board with high thermal conductivity and high temperature resistance, which can meet the needs of high-density integration and high-frequency signal transmission.

CN121398609APending Publication Date: 2026-01-23SUZHOU RIGGER MICRO TECH GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511560873.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-29
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Traditional packaging substrates suffer from poor thermal conductivity, insufficient insulation, and high cost in high-power, high-frequency, and high-temperature scenarios, making them unable to meet the demands of high-density integration and high-frequency signal transmission.

Method used

The co-fired ceramic preparation method is adopted. By preparing ceramic slurry and metal conductor slurry, multilayer green ceramic sheets are formed. After degreasing and sintering, ABF composite layer and solder resist layer are combined to form a ceramic core board with high thermal conductivity and high temperature resistance. Electroplated copper film and ABF composite layer are set on the surface to enhance insulation and interconnection capability.

Benefits of technology

It significantly improves the thermal conductivity and temperature range of the ceramic core board, reduces high-frequency signal loss, improves circuit accuracy and cost-effectiveness, and is suitable for high-power and extreme temperature and humidity scenarios.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a manufacturing method for preparing an organic packaging ceramic substrate from co-fired ceramic, and relates to the technical field of semiconductors. The invention discloses a manufacturing method for preparing an organic packaging ceramic substrate from co-fired ceramic. The manufacturing method comprises the following steps: S110, preparing ceramic slurry and metal conductor slurry; s210, preparing a raw ceramic chip; s310, circuit forming is carried out; s410, carrying out multi-layer lamination; s510, degreasing and sintering are carried out; and S610, post-treatment is carried out. S710, coating the ceramic core plate with a film; and S810, laying a solder mask layer. According to the manufacturing method for preparing the organic packaging ceramic substrate from the co-fired ceramic, the heat conductivity coefficient can be effectively increased, the temperature resistance range is enlarged, and the requirements for high-power heat dissipation and high temperature resistance can be effectively met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor technology, and more specifically, to a method for fabricating organic packaging ceramic substrates using co-fired ceramics. Background Technology

[0002] As chips evolve towards high power, high frequency (such as 5G RF and millimeter-wave radar), and high-density integration (such as Chiplet and HBM), traditional packaging substrates have significant shortcomings: 1. Organic PCB substrates have low thermal conductivity and poor temperature resistance, failing to meet the heat dissipation and high-temperature requirements of high-power chips; 2. Single-metal substrates have poor insulation, requiring additional insulating layers, resulting in complex structures and high high-frequency signal loss; 3. Early high-temperature co-fired ceramic (HTCC) substrates, while exhibiting excellent thermal conductivity and temperature resistance, have high sintering temperatures (1500-1700℃), making them suitable only for high-resistivity conductors such as tungsten and molybdenum, resulting in low circuit precision and high cost; 4. Low-temperature co-fired ceramic (LTCC) substrates, while lowering the sintering temperature (800-950℃) and being suitable for low-resistivity conductors such as silver and copper, suffer from a sharp drop in thermal conductivity due to the addition of a glass phase, making them unable to support heat dissipation for high-power devices; simultaneously, their multi-layer wiring costs remain high. Summary of the Invention

[0003] The purpose of this invention is to provide a method for preparing organic encapsulation ceramic substrates using co-fired ceramics, which can effectively improve the thermal conductivity, increase the temperature resistance range, and effectively meet the requirements of high-power heat dissipation and high-temperature resistance.

[0004] The embodiments of the present invention are implemented as follows: This application provides a method for fabricating an organic encapsulation ceramic substrate using co-fired ceramics, comprising the following steps: S110, Ceramic slurry preparation: Select ceramic powder, mix the ceramic powder with organic binder, plasticizer and solvent in a specific ratio, and prepare a uniform, non-agglomerated ceramic slurry by ball milling or sand milling; Preparation of metal conductor paste: Select conductor powder whose shrinkage rate can be matched with that of the ceramic paste and controlled within ±0.2%, mix the conductor powder with an organic carrier, add glass additives, and then prepare metal conductor paste; S210, Preparation of raw ceramic sheets: The prepared ceramic slurry is uniformly coated on a PET base film, and then the solvent is removed by hot air drying to form a flexible raw ceramic sheet. The raw ceramic sheet is peeled off from the PET base film, cut according to the design size, and inspected for defects such as bubbles, impurities and uneven thickness through optical inspection. Drill through holes at predetermined locations on the raw ceramic tile; The metal conductor paste is filled into the through hole, ensuring that the paste is completely filled without any gaps. After filling, it is pre-dried at low temperature to remove the solvent in the paste. S310, circuit forming; printing the metal conductor paste on the surface of the green ceramic sheet according to a preset circuit pattern, and then performing low-temperature pre-drying to remove the solvent in the paste and form a circuit pattern layer on the surface of the green ceramic sheet; S410, multi-layer stacking; stacking the green ceramic sheets with completed circuit forming according to a design sequence, and tightly combining the layers by pressing to form an integrated multi-layer green body, so as to ensure no gap between the layers; S510, debinding and sintering; removing the organic components in the multi-layer green body to complete debinding; after the debinding is completed, the multi-layer green body is heated at high temperature to diffuse and melt the ceramic powder particles, so as to form a dense ceramic matrix; meanwhile, the metal particles in the metal conductor paste are sintered into a continuous conductor layer, and metallurgical bonding is realized between the ceramic matrix and the conductor layer, so as to form a co-fired ceramic device; S610, post-processing; cutting the co-fired ceramic device after sintering into single ceramic core boards, and polishing and polishing the surface of the single ceramic core board; S710, ceramic core board plating; arranging a copper plating film layer on the surface of the ceramic core board, and arranging an ABF composite layer on the upper surface and the lower surface of the ceramic core board, the ABF composite layer comprising a plurality of ABF layers arranged in layers, and a copper-clad plate layer arranged on the outer side of each ABF layer; a plurality of interconnected pads are formed on the copper-clad plate layer; a plurality of grooves are formed on the copper-clad plate layer, and blind holes are formed on the ABF layer at each groove; a copper pillar is arranged in the blind hole; S810, arranging a solder resist layer; arranging a solder resist layer on the surface of the ABF layer on the outer side, covering the surface treatment layer outside the solder resist layer, and exposing the "pad area" of the solder resist layer window.

[0005] In some embodiments of the present application, in the step S110, the specific ratio is 50-65% of ceramic powder, 5-10% of organic binder, 2-6% of plasticizer, and 15-30% of solvent.

[0006] In some embodiments of the present application, the ceramic powder comprises a low-melting-point ceramic system material, and the ceramic powder is one of borosilicate glass, calcium-aluminum-silicon glass, or alumina / zirconia.

[0007] In some embodiments of the present application, the ceramic powder comprises a high-melting-point ceramic system material, and the ceramic powder is one of alumina or aluminum nitride, and the purity of the alumina is 90%-99.5%.

[0008] In some embodiments of the present application, the ceramic powder further comprises a resistant agent, the resistant agent is resistant to a temperature greater than 1500 DEG C, and the resistant agent is in a powder form.

[0009] In some embodiments of the present application, the conductor powder comprises silver, the particle size of the conductor powder is 0.5-2 μm, and the glass additive is borosilicate glass.

[0010] In some embodiments of the present application, the metal conductor paste formed by mixing the conductor powder with the organic carrier in step S110 has a viscosity of 10,000-50,000 cP.

[0011] In some embodiments of the present application, the hot air drying temperature in step S210 is 60-80°C, and the thickness of the ceramic paste coated on the PET base film is 50-200 μm. In step S210, the low-temperature drying temperature is 60-80°C.

[0012] In some embodiments of the present application, the temperature for the low-temperature pre-drying in step S310 is 80-100°C.

[0013] In some embodiments of the present application, the stacking method of the green ceramic sheet in step S410 includes: normal temperature stacking: stacking under the application of pressure of 10-30 MPa at room temperature; hot-press stacking: stacking under the application of pressure of 5-20 MPa at a temperature of 60-100°C; When the green ceramic sheets are stacked, the through holes and circuit patterns on each layer of the green ceramic sheets need to be aligned, and the alignment error is less than 5 μm.

[0014] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects: 1. Compared with an organic PCB substrate, the thermal conductivity of the ceramic core plate is increased by 150-200 times, the temperature resistance range is expanded to -270-1000°C, and it can be adapted to high-power and extreme temperature and humidity scenes.

[0015] 2. Compared with a single metal substrate, the core plate has a high-insulation ceramic base, does not need an additional insulation layer, and the ABF layer has low dielectric loss, so that the insertion loss of high-frequency signals is reduced by more than 60%.

[0016] 3. Compared with a traditional HTCC substrate, the present application replaces part of the ceramic multilayer wiring with an ABF layer, so that the line precision is increased by 2-5 times, the cost is reduced by 40-60%, and it is compatible with copper low-resistance conductors.

[0017] 4. Compared with a traditional LTCC substrate, the present application can retain high thermal conductivity by adjusting the ceramic formula, and the ABF layer can realize flexible expansion of multilayer wiring, thereby solving the contradiction of "high-frequency adaptation but insufficient high-power heat dissipation" of the LTCC. DETAILED DESCRIPTION

[0021] A method for preparing an organic packaging ceramic substrate by co-firing ceramic includes the following steps: S110, ceramic slurry preparation; select ceramic powder, mix ceramic powder with organic binder, plasticizer and solvent according to specific proportion, and prepare uniform and non-aggregated ceramic slurry through ball milling or sand milling. Specifically, mix ceramic powder, organic binder (such as polyvinyl alcohol, acrylic resin), plasticizer (such as phthalate ester), solvent (such as ethanol, toluene) according to specific proportion, and prepare uniform and non-aggregated ceramic slurry (LTCC commonly uses borosilicate glass-ceramic powder, and HTCC commonly uses alumina and aluminum nitride ceramic powder) through ball milling or sand milling. Avoid pores and cracks after sintering to ensure the mechanical strength (HTCC alumina substrate bending strength can reach more than 300 MPa) and insulation performance (stable dielectric constant and low loss tangent) of the ceramic substrate.

[0022] As can be seen from the above, the ceramic powder is electronic ceramic (such as 90 ceramic, 92 ceramic, 95 ceramic, 96 ceramic or 99 ceramic), glass ceramic, LTCC ceramic, HTCC ceramic, MLCC ceramic, alumina ceramic, aluminum nitride ceramic, silicon nitride ceramic, silicon carbide ceramic or diamond ceramic.

[0023] Among them, LTCC: adopt low melting point glass ceramic system (such as borosilicate glass, calcium aluminum silicon glass and ceramic filler such as alumina / zirconia), the glass phase melts at low temperature, the ceramic particles are bonded and sintered, the overall sintering temperature is reduced, and low melting point metals such as silver (Ag, melting point 961℃) and copper (Cu, melting point 1085℃) are matched.

[0024] HTCC: high purity alumina (Al2O3, purity 90%-99.5%), aluminum nitride (AlN, better thermal conductivity) and other high temperature ceramics as matrix, need to withstand high temperature above 1500℃, so match high melting point metals such as tungsten (W, melting point 3422℃) and molybdenum (Mo, melting point 2623℃) (metals are usually added in the form of carbide powder, and reduced to metal after sintering).

[0025] The above ceramic powder is ground to micron or submicron level (such as LTCC powder particle size 1-5μm) through ball milling to ensure sintering uniformity.

[0026] The above metal conductor slurry is prepared; select the conductor powder which can match the shrinkage rate of the ceramic slurry within ±0.2%, mix the conductor powder with the organic carrier, and prepare the metal conductor slurry after adding the glass additive. The above conductor powder (Ag, Cu, W, etc.) needs to match the shrinkage rate of the ceramic slurry, which is usually realized by adjusting the particle size of the conductor powder (such as Ag powder particle size 0.5-2μm) and adding glass additive (such as LTCC Ag slurry containing a small amount of borosilicate glass to assist sintering bonding).

[0027] S210, green ceramic sheet preparation; the prepared ceramic slurry is uniformly coated on the PET base film, and then hot air drying is performed to remove the solvent, forming a flexible green ceramic sheet, the green ceramic sheet is peeled off from the PET base film, cut according to the design size, and the green ceramic sheet with defects such as bubbles, impurities and uneven thickness is checked out through optical detection. The prepared ceramic slurry is uniformly coated on the PET (polyethylene terephthalate) base tape by the doctor blade of the casting machine, dried by the heating channel (60-80℃) to remove the solvent, and a green ceramic tape (unsintered ceramic sheet) with uniform thickness (usually 50-200μm) is formed; ensure the uniform thickness of the whole after multi-layer stacking, avoid local stress concentration; avoid bubbles or deformation of the ceramic layer caused by violent evaporation of the solvent during sintering; ensure that there is no slurry leakage when filling the metal slurry later, and the via and the circuit are aligned to avoid interconnection failure.

[0028] Step S210 is specifically: Casting: the prepared ceramic slurry is uniformly coated on the PET base film by the doctor blade of the casting machine, and the doctor blade gap (such as 50-200μm, corresponding to the thickness of the green ceramic sheet) is controlled; then the solvent is removed by hot air drying (temperature 50-80℃) to form a flexible green ceramic sheet (thickness precision can be controlled within ±2μm); Cutting and checking: the green ceramic sheet is peeled off from the PET base film, cut according to the design size (such as 50mm×50mm), and defects such as bubbles, impurities and uneven thickness (defects will cause delamination after sintering) are checked out by optical detection (such as CCD); Punching: mechanical punching (suitable for large aperture, such as 100-500μm) or laser punching (suitable for small aperture, such as 20-100μm, higher precision) is adopted to punch through holes at the specified position of the green ceramic sheet; Through hole filling: the metal conductor slurry (consistent with the circuit slurry) is filled into the through hole by screen printing or pressure injection, ensuring that the slurry is completely filled without gaps (gaps will cause increased interconnection resistance or open circuit); low-temperature pre-drying (60-80℃) is required after filling to remove the solvent in the slurry.

[0029] Punching through holes at the predetermined position of the green ceramic sheet; Filling the metal conductor slurry into the through hole, ensuring that the slurry is completely filled without gaps, and pre-drying at low temperature after filling to remove the solvent in the slurry.

[0030] S310, circuit forming; print the metal conductor paste on the surface of the green ceramic sheet according to the preset circuit pattern, and then perform low-temperature pre-drying to remove the solvent in the paste and form a circuit pattern layer on the surface of the green ceramic sheet. Specifically, a screen printing machine (precision ±10 μm) is used to print the metal paste on the surface of the green ceramic strip according to the design pattern to form conductive lines and electrodes; if passive components (such as resistors and capacitors) need to be integrated, resistor paste (such as ruthenium-based paste) or capacitor upper and lower electrode paste is printed at the same time. After printing, it is dried again; the required circuit (such as electrodes, wires, capacitor plates, etc.) is printed on the surface of the green ceramic sheet by screen printing; the conductive performance is consistent, and the problem of local current overheating is avoided; the high-density integration requirement (such as multiple signal lines of 5G radio frequency modules) is met; when the metal conductor paste is uniformly coated on the screen, the paste is transferred to the surface of the green ceramic sheet through the pressure of the scraper (pressure 5-10 N / cm 2 ); after printing, low-temperature drying (80-100°C) is performed again to remove the organic carrier in the paste and form a stable circuit pattern (the thickness of the conductor layer after drying is 10-30 μm) S410, multi-layer stacking; stack the green ceramic sheets with completed circuit formation according to the design order, and tightly combine each layer through pressure to form an integrated multi-layer green body, and ensure that there is no gap between the layers. The specific steps are as follows: stack the green ceramic strips that have completed punching, filling and printing according to the design order, align the interlayer marks (such as positioning holes and cross lines) through an optical alignment system (precision ±2 μm) to ensure that the lines and vias of each layer are accurately matched; avoid interconnection failure caused by line crossing and short circuit or via misplacement (especially for multi-layer LTCC, misplacement will directly damage the radio frequency signal path); ensure that the layers are in close contact to avoid delamination between the layers after sintering; reduce the shrinkage deviation during sintering (the total shrinkage rate of LTCC is usually 12%-18%, and the total shrinkage rate of HTCC is 15%-20%), and ensure the size accuracy of the final product; avoid the generation of gas due to the intense combustion of organic components during sintering, which may cause bubbles, cracking or deformation of the ceramic layer. Stack the green ceramic sheets printed with circuits and punched with vias according to the design order, tightly combine each layer through pressure to form an integrated multi-layer green body, and ensure that there is no gap between the layers (a gap will cause delamination after sintering).

[0031] S510, debinding and sintering; remove the organic components in the multi-layer green body to complete debinding; after debinding, heat the multi-layer green body to make the ceramic powder particles diffuse and melt to form a dense ceramic matrix; at the same time, the metal particles in the metal conductor paste are sintered into a continuous conductor layer, which is metallurgically combined with the ceramic matrix to form a co-fired ceramic device. Debinding and sintering are to ensure excellent insulation performance (volume resistivity ≥10 14 Ω·cm) and mechanical strength; by controlling the heating rate, holding time and cooling rate, the linear shrinkage rate deviation of the product is controlled within ±0.5% to meet the assembly requirements of precision electronic components.

[0032] In the process, the defatting is to remove the organic components, and the green ceramic sheet and the metal paste contain organic components (5%-15%) such as binders and plasticizers. If directly sintered at high temperature, the organic components will quickly burn and produce gas, resulting in cracking, delamination of the ceramic, or bulging of the conductor. Therefore, the low-temperature defatting is needed.

[0033] In the process, the sintering is to make the ceramic densified and combined with the metal components. After the defatting, the multilayer green body enters the high-temperature sintering furnace, and the ceramic powder particles are diffused and melted through high temperature to form a dense ceramic matrix. At the same time, the metal particles in the metal conductor paste are sintered into a continuous conductor layer, and the metal components of the metal conductor paste are combined with the ceramic matrix.

[0034] S610, post-processing; the co-fired ceramic device after sintering is cut and separated into a single ceramic core plate, and the surface of the single ceramic core plate is polished and polished. The purpose is to ensure that the product size meets the design requirements, facilitate subsequent assembly, avoid mechanical strength reduction caused by ceramic edge cracking (especially in the field of aerospace, edge defects can cause stress concentration and affect reliability), ensure that the electrical performance and reliability of the product meet the standards, and fine-tune the built-in resistors, capacitors and other components (such as laser resistance repair) to ensure that the parameter deviation is within the design range.

[0035] The co-fired ceramic device after sintering needs to be optimized in performance through post-processing and strictly detected for defects to ensure that it meets the application requirements; Surface treatment: if the device surface needs to be welded with external pins, metalization treatment needs to be performed on the external electrode area (such as LTCC device electroplating nickel (Ni) + gold (Au) to improve welding reliability and oxidation resistance); Cutting and shape processing: if "whole plate sintering" (multiple devices integrated) is adopted during sintering, the whole plate needs to be cut into single devices through laser cutting or diamond grinding wheel cutting; Polishing and polishing: for devices with high surface flatness requirements (such as ceramic substrates), chemical mechanical planarization (CMP) or mechanical polishing is needed to make the surface roughness Ra<0.1 μm.

[0036] Structure detection: X-ray (X-Ray) is used to detect the internal via filling and whether the layers are delaminated; scanning electron microscope (SEM) is used to observe the ceramic density (the density needs to be >95%) and the metal-ceramic interface bonding state; Electrical performance detection: the circuit conduction, insulation resistance (such as LTCC device insulation resistance >10 12 Ω), dielectric constant (such as Al2O3, HTCC dielectric constant ≈9.8), loss tangent (tanδ<0.001) are tested; Thermal performance test: test thermal conductivity (e.g. AlN HTCC thermal conductivity > 150 W / (m・K)), thermal resistance (θJA); Mechanical performance test: test bending strength (e.g. Al2O3, HTCC bending strength > 300 MPa), hardness (Vickers hardness > 1200 HV).

[0037] S710, ceramic core plate plating; a copper electroplating film layer is arranged on the surface of the ceramic core plate, and an ABF composite layer is arranged on the upper surface and the lower surface of the ceramic core plate, the ABF composite layer comprises a plurality of ABF layers arranged in layers, and a copper-clad plate layer is arranged on the outer side of each ABF layer; a plurality of interconnected pads are formed on the copper-clad plate layer; a plurality of grooves are formed on the copper-clad plate layer, and blind holes are formed on the ABF layers at the grooves; a copper column is arranged in the blind hole. A plurality of interconnected holes are arranged on the ceramic core plate, the interconnected holes penetrate the upper and lower surfaces of the ceramic core plate; a copper electroplating film layer is arranged on the upper surface and the lower surface of the ceramic core plate and the hole wall of the interconnected hole; and the interconnected hole is filled with ink.

[0038] The copper film arranged on the surface of the ceramic core plate is a key link for connecting the "insulation / high reliability substrate characteristics" of the ceramic core plate and the "conductive / interconnection demand" of external electronic elements; although the surface of the ceramic core plate is hard, it has micro pores or defects and is easy to be damaged by external environment (such as humidity, chemical corrosion) or mechanical stress (such as pressing during assembly), and the copper film can play a "protective layer" role.

[0039] This step S710 makes up for the short board of the ceramic material in high-density wiring, cost control and packaging compatibility, while retaining the core advantages of the ceramic core plate; the ABF composite layer has good flexibility and compatibility, and can carry passive elements (resistor, capacitor, inductor) on its surface or inside, or as a "transition layer" to connect the ceramic core plate and other organic substrates (such as PCB), solving the "rigid matching" problem of ceramic and organic materials. Specifically, in terms of performance, it will take into account "high-speed signal integrity" and "high heat dissipation"; in terms of reliability, it can improve the "thermal stress matching" and "mechanical protection" capabilities.

[0040] S810, a solder resist layer is arranged; a solder resist layer is arranged on the surface of the ABF layer on the outer side, the surface treatment layer covers the outer side of the solder resist layer, and the "pad area" of the solder resist layer is exposed. The role of this step is to protect the ABF layer and the copper wiring: to isolate external damage and environmental erosion; during the packaging process, welding needs to be performed on the copper pad of the ABF layer (such as chip bump welding, SolderBall ball mounting, passive element mounting), and the solder resist layer precisely defines the welding area through "window design"; the ABF layer itself has low hardness (Shore hardness D ≈ 60-70), and is easily scratched during packaging and pressing; the solder resist layer has high hardness (Shore hardness D ≈ 85-90) after curing, and can resist slight mechanical friction or impact, protecting the ABF layer and the copper wiring from physical damage; the exposed copper pad in the window area is treated by roughening, and the wettability (contact angle ≤ 30°) with the solder is significantly improved, which can reduce defects such as false welding and cold welding; at the same time, the solder resist layer can block the spread of solder to non-pad areas, ensuring that the volume (such as SolderBall diameter deviation ≤ ± 10%) and shape of the solder joints meet the packaging requirements, and improving the welding reliability; the completely cured solder resist layer has excellent resistance to humidity and heat (after being placed in an environment of 85°C / 85%RH for 1000 hours, the coating has no blistering, peeling, and the copper wiring has no corrosion), resistance to chemicals (can withstand immersion in commonly used cleaning agents such as soldering flux, alcohol, acetone), avoiding failure of the ABF layer and the copper wiring due to environmental factors.

[0041] In addition, the outer side of the solder resist layer is provided with a surface treatment layer, which needs to cover the outer side of the solder resist layer and only expose the "pad area" of the solder resist layer (for subsequent chip welding or interconnection of the substrate and the PCB); the core role of the surface treatment layer is to solve the performance defects of the "pad on the outer side of the solder resist layer", and to connect the subsequent packaging process.

[0042] The copper pad of the solder resist layer is directly exposed to the air and is easily oxidized (CuO / Cu2O is formed), and the oxidized copper pad cannot form reliable bonding with the solder (such as solder paste and gold wire). The packaging substrate needs to adapt to different application scenarios (such as the humid and hot environment of consumer electronics and the high and low temperature cycle of automotive electronics), and the surface treatment layer can resist external environmental erosion; the ABF composite layer (organic resin base) and the solder resist layer (epoxy resin base) are both organic materials, and the surface treatment layer can indirectly protect their structures; different surface treatment layers can match different welding / bonding processes, improving the versatility of the substrate.

[0043] In some embodiments of the application, in the step S110, the specific proportions are 50-65% of ceramic powder, 5-10% of organic binder, 2-6% of plasticizer, and 15-30% of solvent.

[0044] In some embodiments of the present application, the ceramic powder described above comprises low melting point ceramic system material, and the ceramic powder is one of borosilicate glass, calcium alumino-silicate glass or alumina / zirconia.

[0045] In some embodiments of the present application, the ceramic powder described above comprises high melting point ceramic system material, and the ceramic powder is one of alumina or aluminum nitride, and the purity of the alumina is 90%-99.5%.

[0046] In some embodiments of the present application, the ceramic powder described above further comprises a temperature-resistant agent, and the temperature-resistant agent is resistant to a temperature greater than 1500℃, and the temperature-resistant agent is in powder form.

[0047] In some embodiments of the present application, the conductor powder described above comprises silver, and the particle size of the conductor powder is 0.5-2μm, and the glass aid is borosilicate glass.

[0048] In some embodiments of the present application, in the step S110 described above, the viscosity of the metal conductor paste formed after the mixing of the conductor powder and the organic carrier is 10000-50000cP, which can ensure the flowability and formability during printing.

[0049] In some embodiments of the present application, in the step S210 described above, the temperature of the hot air drying is 60℃-80℃, and the thickness of the ceramic paste coated on the PET base film is 50-200μm.

[0050] In some embodiments of the present application, in the step S210 described above, the temperature of the low-temperature drying is 60℃-80℃.

[0051] In some embodiments of the present application, in the step S310 described above, the temperature of the low-temperature pre-drying is 80℃-100℃.

[0052] In some embodiments of the present application, in the step S410 described above, the stacking mode of the green ceramic sheet comprises: Room temperature stacking: stacking under the application of pressure of 10-30MPa at room temperature, which is suitable for LTCC green ceramic sheets (high content of adhesive, good flexibility).

[0053] Hot-press stacking: stacking under the application of pressure of 5-20MPa at a temperature of 60℃-100℃, which is suitable for HTCC green ceramic sheets (low content of adhesive, need to be heated to soften to assist bonding) When the green ceramic sheets are stacked, the through holes and circuit patterns on each layer of the green ceramic sheets need to be aligned, and the alignment error is less than 5μm. The alignment of the through holes and circuit patterns of each layer is ensured by positioning pins or an optical alignment system (the alignment error needs to be <5μm, otherwise the through holes and circuit will be misaligned, and the interconnection will fail).

[0054] Example 1 The embodiment provides a manufacturing method of an organic packaging ceramic substrate prepared by co-firing ceramics, and comprises the following steps. S110, ceramic slurry preparation; ceramic powder is selected, the ceramic powder is mixed with an organic binder, a plasticizer and a solvent in a specific proportion, and a uniform and non-agglomerated ceramic slurry is prepared through ball milling or sand milling. The organic binder is polyvinyl alcohol, the plasticizer is phthalate, and the solvent is ethanol.

[0055] Metallic conductor slurry preparation; a conductor powder capable of matching the shrinkage rate of the ceramic slurry within a difference control range of ±0.2% is selected, the conductor powder is mixed with an organic carrier, and a metallic conductor slurry is prepared after adding a glass additive; S210, green ceramic sheet preparation; the prepared ceramic slurry is uniformly coated on a PET base film, and then hot air drying is performed to remove the solvent, so that a flexible green ceramic sheet is formed; the green ceramic sheet is peeled off from the PET base film, cut according to a design size, and subjected to optical detection to check the green ceramic sheet for defects such as bubbles, impurities and uneven thickness; A through hole is punched at a predetermined position of the green ceramic sheet; The metallic conductor slurry is filled into the through hole, so that the slurry is completely filled without any gap; and low-temperature pre-drying is performed after the filling, so that the solvent in the slurry is removed; S310, circuit forming; the metallic conductor slurry is printed on the surface of the green ceramic sheet according to a preset circuit pattern, and then low-temperature pre-drying is performed to remove the solvent in the slurry, so that a circuit pattern layer is formed on the surface of the green ceramic sheet; S410, multi-layer superposition; the green ceramic sheet on which the circuit forming is completed is stacked in a design order, and each layer is tightly combined through pressing, so that an integrated multi-layer green body is formed, and no gap is ensured between the layers; S510, debinding and sintering; the organic components in the multi-layer green body are removed to complete debinding; after the debinding is completed, the multi-layer green body is heated at a high temperature, so that the ceramic powder particles diffuse and melt to form a dense ceramic matrix; meanwhile, the metal particles in the metallic conductor slurry are sintered into a continuous conductor layer, and metallurgical bonding is realized between the ceramic matrix and the conductor layer, so that a co-firing ceramic device is formed; S610, post-processing; the co-firing ceramic device after sintering is cut and separated into single ceramic core boards, and the surface of each single ceramic core board is polished and polished; S710, ceramic core board plating; a copper plating layer is arranged on the surface of the ceramic core board, and ABF composite layers are arranged on the upper surface and the lower surface of the ceramic core board; the ABF composite layers comprise a plurality of ABF layers arranged in a stack; a copper clad plate layer is arranged on the outer side of each ABF layer; a plurality of communication pads are formed on the copper clad plate layer; a plurality of grooves are formed on the copper clad plate layer, and blind holes are formed on the ABF layers at the grooves; and copper pillars are arranged in the blind holes. S810, disposing a solder resist layer; disposing a solder resist layer on the surface of the ABF layer on the outer side, covering the surface treatment layer on the outer side of the solder resist layer, and exposing the "pad area" of the solder resist layer window.

[0056] In the step S110, the specific proportion is 50-65% of ceramic powder, 5-10% of organic binder, 2-6% of plasticizer, and 15-30% of solvent.

[0057] In the step S110, the ceramic powder includes low-melting-point ceramic system material, and the ceramic powder is borosilicate glass.

[0058] In the step S110, the ceramic powder includes high-melting-point ceramic system material, and the ceramic powder is alumina with a purity of 90%.

[0059] In the step S110, the ceramic powder further includes a resistant agent, the resistant agent is resistant to a temperature greater than 1500℃, and the resistant agent is in powder form. The resistant agent is tungsten metal.

[0060] In the step S110, the conductor powder includes silver, the particle size of the conductor powder is 0.5-2μm, and the glass aid is borosilicate glass.

[0061] In the step S110, the viscosity of the metal conductor paste formed by mixing the conductor powder and the organic carrier is 10000cP.

[0062] In the step S210, the hot air drying temperature is 60℃, and the thickness of the ceramic paste coated on the PET base film is 50μm.

[0063] In the step S210, the low-temperature drying temperature is 60℃.

[0064] In the step S310, the temperature of the low-temperature pre-drying is 80℃.

[0065] In the step S410, the stacking mode of the green ceramic sheet includes: Room temperature stacking; stacking under the condition of applying a pressure of 10MPa at room temperature; Hot pressing stacking; stacking under the condition of applying a pressure of 5MPa at 60℃; When the green ceramic sheet is stacked, the through holes and circuit patterns on each layer of the green ceramic sheet need to be aligned, and the alignment error is less than 5μm.

[0066] Example 2 The embodiment provides a manufacturing method of a co-fired ceramic organic packaging ceramic substrate, including the following steps: S110, ceramic slurry preparation; select ceramic powder, mix the ceramic powder with organic binder, plasticizer and solvent according to specific proportion, and make uniform and non-agglomerated ceramic slurry through ball milling or sand milling. The organic binder is polyvinyl alcohol, the plasticizer is phthalate, and the solvent is ethanol.

[0067] Metallic conductor slurry preparation; select a conductor powder that can match the shrinkage rate of the ceramic slurry within a difference of ±0.2%, mix the conductor powder with an organic carrier, and then add a glass aid to prepare a metallic conductor slurry; S210, green ceramic sheet preparation; uniformly coat the prepared ceramic slurry on a PET base film, then perform hot air drying to remove the solvent, form a flexible green ceramic sheet, peel the green ceramic sheet from the PET base film, cut according to the design size, and detect and exclude defective green ceramic sheets such as bubbles, impurities and uneven thickness through optical detection; Drill a through hole at a predetermined position of the green ceramic sheet; Fill the metallic conductor slurry into the through hole, ensure that the slurry is completely filled without gaps, and perform low-temperature pre-drying after filling to remove the solvent in the slurry; S310, circuit forming; print the metallic conductor slurry on the surface of the green ceramic sheet according to the preset circuit pattern, and then perform low-temperature pre-drying to remove the solvent in the slurry, thereby forming a circuit pattern layer on the surface of the green ceramic sheet; S410, multi-layer stacking; stack the green ceramic sheets with completed circuit forming according to the design order, tightly bond each layer through pressing, and form an integrated multi-layer green body to ensure that there is no gap between the layers; S510, debinding and sintering; remove the organic components in the multi-layer green body to complete debinding; after debinding, diffuse and melt the ceramic powder particles in the multi-layer green body through high-temperature heating to form a dense ceramic matrix; at the same time, the metal particles in the metallic conductor slurry are sintered into a continuous conductor layer, which is metallurgically combined with the ceramic matrix to form a co-fired ceramic device; S610, post-processing; cut the sintered co-fired ceramic device into single ceramic core boards, and polish and polish the surface of the single ceramic core boards; S710, ceramic core board plating; set a copper plating layer on the surface of the ceramic core board, and then set an ABF composite layer on the upper surface and the lower surface of the ceramic core board. The ABF composite layer includes a plurality of ABF layers arranged in layers, and a copper-clad plate layer is arranged on the outer side of each ABF layer. A plurality of interconnected pads are formed on the copper-clad plate layer. A plurality of grooves are formed on the copper-clad plate layer, and blind holes are formed on the ABF layer at each groove. A copper pillar is arranged in the blind hole. S810, layout of solder resist layer; a solder resist layer is arranged on the surface of the ABF layer located on the outer side, a surface treatment layer is covered on the outer side of the solder resist layer, and a "pad area" of the solder resist layer is exposed.

[0068] In the step S110, the specific proportion is 50-65% of the ceramic powder, 5-10% of the organic binder, 2-6% of the plasticizer and 15-30% of the solvent.

[0069] In the step S110, the ceramic powder includes low melting point ceramic system material, and the ceramic powder is borosilicate glass.

[0070] In the step S110, the ceramic powder includes high melting point ceramic system material, and the ceramic powder is alumina with a purity of 90-99.5%.

[0071] In the step S110, the ceramic powder further includes a resistant agent, the resistant agent is resistant to a temperature greater than 1500℃, and the resistant agent is in powder form. The resistant agent is tungsten metal.

[0072] In the step S110, the conductor powder includes silver, the particle size of the conductor powder is 1.25μm, and the glass aid is borosilicate glass.

[0073] In the step S110, the viscosity of the metal conductor slurry formed after the mixing of the conductor powder and the organic carrier is 30000cP.

[0074] In the step S210, the hot air drying temperature is 70℃, and the thickness of the ceramic slurry coated on the PET base film is 125μm.

[0075] In the step S210, the low temperature drying temperature is 70℃.

[0076] In the step S310, the temperature of the low temperature pre-drying is 90℃.

[0077] In the step S410, the stacking mode of the green ceramic sheet includes: Room temperature stacking: stacking under the application of pressure 20MPa at room temperature; Hot pressing stacking: stacking under the application of pressure 12.5MPa at 80℃; In the step S410, the through holes and the circuit patterns on each layer of the green ceramic sheet need to be aligned, and the alignment error is less than 5μm.

[0078] Example 3 The present embodiment provides a method for preparing an organic packaging ceramic substrate by co-firing ceramics, which comprises the following steps: S110, ceramic slurry preparation: selecting ceramic powder, mixing the ceramic powder with an organic binder, a plasticizer and a solvent according to a specific proportion, and preparing a uniform and non-agglomerated ceramic slurry by ball milling or sand milling. The organic binder is specifically acrylic resin, the plasticizer is specifically phthalate, and the solvent is specifically toluene.

[0079] Metallic conductor paste preparation; select a conductor powder that can match the shrinkage rate of the ceramic paste within a difference of ±0.2%, mix the conductor powder with the organic carrier, add a glass additive, and prepare a metallic conductor paste; S210, green ceramic sheet preparation; uniformly coat the prepared ceramic paste on the PET base film, then perform hot air drying to remove the solvent, form a flexible green ceramic sheet, peel the green ceramic sheet from the PET base film, cut according to the design size, and check for defects such as bubbles, impurities, and uneven thickness of the green ceramic sheet through optical detection; Drill a through hole at a predetermined position of the green ceramic sheet; Fill the metallic conductor paste into the through hole, ensure that the paste is completely filled without gaps, and perform low-temperature pre-drying after filling to remove the solvent in the paste; S310, circuit formation; print the metallic conductor paste on the surface of the green ceramic sheet according to the pre-set circuit pattern, and then perform low-temperature pre-drying to remove the solvent in the paste, thereby forming a circuit pattern layer on the surface of the green ceramic sheet; S410, multi-layer stacking; stack the green ceramic sheets with completed circuit formation in the designed order, tightly bond each layer through pressing, and form an integrated multi-layer green body to ensure that there is no gap between the layers; S510, debinding and sintering; remove the organic components in the multi-layer green body to complete debinding; after debinding, heat the multi-layer green body at high temperature to diffuse and melt the ceramic powder particles, thereby forming a dense ceramic matrix; at the same time, the metal particles in the metallic conductor paste are sintered into a continuous conductor layer, which is metallurgically combined with the ceramic matrix to form a co-fired ceramic device; S610, post-processing; cut the sintered co-fired ceramic device into individual ceramic core boards, and polish and polish the surface of the individual ceramic core boards; S710, ceramic core board plating; set a copper plating film layer on the surface of the ceramic core board, and then set an ABF composite layer on the upper and lower surfaces of the ceramic core board, the ABF composite layer includes a plurality of ABF layers arranged in layers, and a copper-clad plate layer is arranged on the outer side of each ABF layer; a plurality of interconnected pads are formed on the copper-clad plate layer; a plurality of grooves are formed on the copper-clad plate layer, and blind holes are formed on the ABF layer at each groove; a copper pillar is arranged in the blind hole; S810, layout of the solder resist layer; a solder resist layer is arranged on the surface of the ABF layer located on the outer side, a surface treatment layer is covered on the outer side of the solder resist layer, and the "pad area" of the solder resist layer is exposed.

[0080] In the step S110, the specific proportions are 50-65% of ceramic powder, 5-10% of organic binder, 2-6% of plasticizer, and 15-30% of solvent.

[0081] The ceramic powder includes a low-melting-point ceramic system material, and the ceramic powder is borosilicate glass.

[0082] The ceramic powder includes a high-melting-point ceramic system material, and the ceramic powder is alumina with a purity of 99.5%.

[0083] The ceramic powder further includes a refractory agent, the refractory agent is resistant to a temperature greater than 1500℃, and the refractory agent is in a powder form. The refractory agent is tungsten metal.

[0084] The conductor powder includes silver, the particle size of the conductor powder is 2μm, and the glass aid is borosilicate glass.

[0085] In the step S110, the viscosity of the metal conductor slurry formed by mixing the conductor powder and the organic carrier is 50000cP.

[0086] In the step S210, the temperature of the hot air drying is 80℃, and the thickness of the ceramic slurry coated on the PET base film is 200μm.

[0087] In the step S210, the temperature of the low-temperature drying is 80℃.

[0088] In the step S310, the temperature of the low-temperature pre-drying is 100℃.

[0089] In the step S410, the stacking mode of the green ceramic sheet includes: Room-temperature stacking: stacking under a pressure of 30MPa at room temperature; Hot-press stacking: stacking under a pressure of 20MPa at a temperature of 100℃; In the stacking of the green ceramic sheet, the through holes and the circuit patterns on each layer of the green ceramic sheet are aligned, and the alignment error is less than 5μm.

[0090] The above only describes the preferred embodiments of the present application and is not used to limit the present application. For those skilled in the art, the present application can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for manufacturing an organic package ceramic substrate by co-firing ceramics, characterized by, The method comprises the following steps: S110, ceramic slurry preparation; selecting ceramic powder, mixing the ceramic powder with organic binder, plasticizer and solvent in a specific proportion, and preparing uniform and non-agglomerated ceramic slurry through ball milling or sand milling; Metallic conductor slurry preparation; selecting a conductor powder that can match the shrinkage rate of the ceramic slurry with a difference controlled within ±0.2%, mixing the conductor powder with an organic carrier, and preparing a metallic conductor slurry after adding a glass additive; S210, green ceramic sheet preparation; uniformly coating the prepared ceramic slurry on a PET base film, then performing hot air drying to remove the solvent, forming a flexible green ceramic sheet, peeling the green ceramic sheet from the PET base film, cutting according to the design size, and checking the green ceramic sheet for defects such as bubbles, impurities and uneven thickness through optical detection; Punching a through hole at a predetermined position of the green ceramic sheet; Filling the metallic conductor slurry into the through hole, ensuring that the slurry is completely filled without gaps, and performing low-temperature pre-drying after filling to remove the solvent in the slurry; S310, circuit forming; Printing the metallic conductor slurry on the surface of the green ceramic sheet according to a preset circuit pattern, and then performing low-temperature pre-drying to remove the solvent in the slurry, thereby forming a circuit pattern layer on the surface of the green ceramic sheet; S410, multi-layer stacking; Stacking the green ceramic sheets with completed circuit forming in a designed order, tightly combining each layer through pressing to form an integrated multi-layer green body, and ensuring that there is no gap between the layers; S510, debinding and sintering; removing the organic components in the multi-layer green body to complete debinding; after debinding, diffusing and melting the ceramic powder particles in the multi-layer green body through high-temperature heating to form a dense ceramic matrix; at the same time, sintering the metal particles in the metallic conductor slurry into a continuous conductor layer, and realizing metallurgical bonding with the ceramic matrix to form a co-fired ceramic device; S610, post-processing; cutting the sintered co-fired ceramic device into single ceramic core boards, and polishing and polishing the surface of the single ceramic core boards; S710, ceramic core board plating; setting a copper plating film layer on the surface of the ceramic core board, and arranging an ABF composite layer on the upper surface and the lower surface of the ceramic core board, the ABF composite layer comprising a plurality of ABF layers arranged in layers, and a copper-clad plate layer arranged on the outer side of each ABF layer; a plurality of interconnected pads are formed on the copper-clad plate layer; a plurality of grooves are formed on the copper-clad plate layer, and blind holes are formed on the ABF layer at each groove; a copper pillar is arranged in the blind hole; S810, arranging a solder resist layer; arranging a solder resist layer on the surface of the ABF layer on the outer side, covering the surface treatment layer outside the solder resist layer, and exposing the "pad area" of the solder resist layer window.

2. The method of claim 1, wherein the organic package ceramic substrate is prepared by a co-firing ceramic process. In the step S110, the specific proportion is 50-65% of ceramic powder, 5-10% of organic binder, 2-6% of plasticizer and 15-30% of solvent.

3. The method of claim 1, wherein the organic package ceramic substrate is prepared by a co-firing ceramic process. The ceramic powder comprises a low-melting-point ceramic system material, and the ceramic powder is one of borosilicate glass, calcium alumino-silicate glass or alumina / zirconia.

4. The method of claim 1, wherein the organic package ceramic substrate is prepared by co-firing. The ceramic powder comprises a high-melting-point ceramic system material, and the ceramic powder is one of alumina, aluminum nitride, silicon nitride or diamond, and the purity of the alumina is 90-99.5%.

5. The method of claim 4, wherein the organic package ceramic substrate is prepared by co-firing. 5 The ceramic powder further comprises a resistant agent, the resistant agent is resistant to temperature greater than 1500 DEG C, and the resistant agent is in powder form.

6. The method of claim 1, wherein the organic package ceramic substrate is prepared by co-firing ceramics. The conductor powder comprises silver, the particle size of the conductor powder is 0.5-2 μm, and the glass aid is borosilicate glass.

7. The method of claim 1, wherein the organic package ceramic substrate is prepared by a co-firing ceramic process. In the step S110, the viscosity of the metal conductor slurry formed by mixing the conductor powder and the organic carrier is 10000-50000 cP.

8. The method of claim 1, wherein the organic package ceramic substrate is prepared by a co-firing ceramic process. In the step S210, the hot air drying temperature is 60-80 DEG C, the thickness of the ceramic slurry coated on the PET base film is 50-200 μm, and the low temperature drying temperature is 60-80 DEG C.

9. The method of claim 1, wherein the organic package ceramic substrate is prepared by a co-firing ceramic process. In the step S310, the temperature of the low temperature pre-drying is 80-100 DEG C.

10. The method of claim 1, wherein the organic package ceramic substrate is prepared by a co-firing ceramic process. In the step S410, the stacking mode of the green ceramic sheet comprises: Normal temperature stacking; stacking under the condition of applying pressure of 10-30 MPa at room temperature; Hot pressing stacking; stacking under the condition of applying pressure of 5-20 MPa at 60-100 DEG C; When the green ceramic sheet is stacked, the through hole and the circuit pattern on each layer of the green ceramic sheet need to be aligned, and the alignment error is less than 5 μm.